RESILIENCIA Y CONSUMO DE DROGAS. UN ESTUDIO EN JÓVENES COSTARRICENSES - Méndez Muñoz, Jesús (2018)
The aim of this study was to determine the factors associated with drug (use) abstention (or drug non-use). For this purpose, in addition to a variety of instruments, it was administered a scale of resilience which identified risk and protective factors in two selected samples intentionally in the Gran Área Metropolitana (GAM), in order to establish if the substance was or not associated with higher or lower values of resilience. The use of logistic regression models and factor analysis allowed to establish the absence of significant relationships between levels of resilience and abstinence or ingestion of various drugs.